Effect of Giving Health Education About Decompression Disease on Knowledge of Traditional Fisherman - Ira Sandi Tunny; Sely M. Dahlan; Zein Lukman (Health Notions, 2017)
One of disease that related to traditional fisherman is decompression disease. Decompression disease is disease with many various of complain and symptoms, those could disturb all of body system with same caused is nitrogen occurred in tissue and blood. This research purpose to know effect of giving health education about decompression disease to traditional fisherman knowledge at RT 06 in western seram districh, tanah goyang hamlet. Type of research is quasi experimental research with pre individual pra post test design. Sample has taken by total sampling amounted 40 head families as traditional fisherman. Data analyzet with paired t test. Result showed that knowledge variable pre test with p value 0,041 and knowledge with p value after giving health education equal 0.000. It was mean relation with incident of decompression disease.from the result, can be concluded that there was effect giving health educationabout decompression disease to traditional fisherman knowledge level at RT 06 in western seram district, tanah goyang hamlet. Keywords: Health education, Decompression disease